Crianças maravilhosas: brincadeiras, imaginação e culturas de infâncias numa turma do terceiro ano do Ensino Fundamental de uma escola pública - Balduino, Grazielle Eloísa (2014)
The present research was produced with the children of a group of third grade of elementary school in a school Hall in the city of Uberlandia, Minas Gerais, during the year of 2013. This institution is located in a peripheral region of the city considered by the city and military police a neighborhood with considerable content of violence and drug trafficking. In this research we seek to know and understand children s actions, their feelings, their needs and possibilities in space-time of the school questioned the position of this institution that this class was weak and had difficulty in learning; however, the ways of being and acting of these kids informed us about children s cultures. Cultures of childhoods are produced, (re) produced and shared between them and with the adults in the school routine; specifically within the school, the children become members both of their cultures as cultures pairs of adults. How to reach the kids? That way you can promote encounters between adults and children, in such a way that we can get to know them better? The extent to which games and children s activities promoted in space-school time build and express the children s cultures? These questions were the guiding of the construction process of this investigation that presents itself as a qualitative research, which has opted for dialogue and an intense interaction with the children as a means through which we were able to confirm that they are subjects of culture in many surprising ways. Built during the school year 2013, along with kids, playful activities that expressed a process of partnership and friendship. The playground proved the space time richer children s production; the absence of Professor Regent also proved important as a condition for children to feel more free to act guided by their interests.